A Robust Missing Data-Recovering Technique for Mobility Data Mining. Issue 5 (3rd July 2017) - Zafar, Annam; Kamran, Muhammad; Shad, Shafqat Ali; Nisar, Wasif
ABSTRACT: Based on location information, users' mobility profile building is the main task for making different useful systems such as early warning system, next destination and route prediction, tourist guide, mobile users' behavior-aware applications, and potential friend recommendation. For mobility profile building, frequent trajectory patterns are required. The trajectory building is based on significant location extraction and the user's actual movement prediction. Previous works have focused on significant places extraction without considering the change in GSM (global system for mobile communication) network and is based on complete data analysis. Since network operators change the GSM network periodically, there are possibilities of missing values and outliers. These missing values and outliers must be addressed to ensure actual mobility and for the efficient extraction of significant places, which are the basis for users' trajectory building. In this paper, we propose a methodology to convert geo-coordinates into semantic tags and we also purposed a clustering methodology for recovering missing values and outlier detection. Experimental results prove the efficiency and effectiveness of the proposed scheme.